REPRESENTASI BUDAYA DALAM NOVEL HUJAN BULAN JUNI KARYA SAPARDI DJOKO DAMONO - Amelia, Nenden Rizky; Rahayu, Lina Meilinawati; Aksa, Yati (JURNAL PESONA, 2017)
This paper is determine representation about culture in the Hujan Bulan Juni novel by Sapardi Djoko Damono. This paper based in the issue that comes from the novel related to the chracteristic of Javanese and Manado culture. The aim of this paper is to describe culture representation that shows by the concept of this novel. This explanation based on the theory about Javanese peopleâs characteristic from Geertz, Manado peopleâs characteristic from Sumampow and concept culuture identity from Hall and Woodward. The result ofÂ  the analysis shows that the novel displays the cultural characteristics of Java wich is different for each character. The âethok-ethokâ (pretend), âwediâ(afraid),â isinâ(shame), dan âsungkanâ attitude displayed by the character that has the constancy of identity. While being open, straight foward and aggressive attitude. While Manado characters are represented through characters steady by showing agrressive attitude, overt, brave, culinary practice, character name and Christianity. Different cultural characteristics to each person indicate the liquid identity.Â